Isolation and Identification of Emestrin from Emericella nidulans and Investigation of Its Anticancer Properties - MUHAMMAD NURSID; EKOWATI CHASANAH; . MURWANTOKO; SUBAGUS WAHYUONO (Microbiology Indonesia, 2011)
The research to isolate, identify and investigate of anticancer properties of active compound produced by Emericella nidulans marine fungus has been done. Active compound was isolated from mycelium extract of the  fungus. The molecular formula of active compound was established as C27H21N2O10S2 by LC-ESI-ToF-MS (m/z 597.1105 [M – H]-. Elucidation of molecular structure using FT-IR, LC-ESI-ToF-MS, 1H-NMR, 13C-NMR, and DEPT 135˚ showed that the active compound was emestrin. Emestrin was found to have cytotoxic effect against T47D, HepG2, C28, and HeLa but it was not too toxic against Vero cells with IC50 value of 1.8 µg mL-1, 4.2 µg mL-1, 2.6 µg mL-1, 13.8 µg mL-1, and 260.9 μg mL-1, respectively. Base on the cell cycle analysis by using flow cytometry, emestrin treatment at concentration of 1.0 μg mL-1 induced cell-cycle arrest in G0/G1 phase whereas at concentration of 3.0 μg mL-1, a sub-population of cells (sub G1) appeared. The apoptosis assay by using Annexin-V-FLUOS revealed that most of T47D cell treated with the compound at 1.0 and 3.0 μg mL-1 underwent apoptosis (83.6% and 92.6%, respectively. This anticancer activity of emestrin may be related to the unique of the epithiodioxopiperazine moiety with internal disulphide bond of this compound.